(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Multiple sclerosis (MS) is a chronic immune-mediated demyelinating disease of the central nervous system characterized by inflammation, demyelination, and neurodegeneration. Due to the heterogeneity of clinical manifestations and the absence of a single pathognomonic test, early and accurate diagnosis remains a major clinical challenge. The introduction of the McDonald diagnostic criteria has significantly improved diagnostic accuracy by integrating clinical, radiological, and laboratory findings. This thesis reviews the current diagnostic criteria for multiple sclerosis, emphasizing the role of magnetic resonance imaging (MRI), cerebrospinal fluid (CSF) analysis, and evidence of dissemination in space and time.